The Impact of the Value of Religiosity on Buying Decision Making on the Overseas Bugis Community in Jambi - Kurniati Karim; Ahmad Hosen (International Journal of Science, Technology & Management, 2020)
The Bugis tribe is one of the tribes in South Sulawesi Province, in addition to the Makassar and Toraja tribes, who uphold their religion and become the basis for their behavior. This is in accordance with the Bugis philosophy of "MappesonariDewataseuwae” (surrender to God's will), which means that the Buginese people behave according to the religious values derived from their culture.The Bugistribe inhabit almost all corners of the archipelago, including in Sumatra, especially Jambi. By inhabiting the Jambi area, it is certain that the influence of the local culture will certainly affect the behavior of someone who lives in the area.Considering that, then, the purpose of this study is to analyze the influence of the value of religiosity of the Bugis tribe in Jambi on the decision of purchasing products.To answer the research problem, the data were collected through a questionnaire of 106 people, then analyzed using simple linear regression analysis. The research results obtained, that although the Bugis people have settled in Jambi, Sumatra, but the decision to purchase products is still influenced by the value of religiosity.